Marketing Strategy of Weight-Loss Management Product: A Case of Wellness and Healthcare Industry in the Klang Valley, Malaysia - Chua, Siok Yoong (2024)
Incorporating health and wellness principles is essential for a holistic approach to sustainable weight loss management, ensuring balance across various aspects such as physical, social, spiritual, emotional, intellectual, environmental, and occupational dimensions. Despite the challenges of the COVID-19 pandemic, the global wellness industry surpassed USD$5.6 trillion in demand by 2022, with segments like healthy eating, nutrition, and weight loss showing consistent growth that reflects evolving consumer preferences. In Malaysia, the increasing prevalence of non-communicable diseases highlights the importance of the weight management and well-being market, which grew by 8% in 2023 and is expected to maintain a 7.7% compound annual growth rate (CAGR) until 2028. However, despite consumer growing reliance on meal replacement products for weight management, there remains a dearth of research into their long-term effectiveness and limitations. This qualitative study employs an ex-post facto design and a strategic research approach, in a growing brand-diversity of wellness-healthcare market, to review and analyse the product-effective challenges of three leading weight management brands experiencing market-share decline: Cambridge weight management program, Herbalife weight management program, and Isowhey weight management program. It investigates the program protocols, user feedback, and insights from brand experts, revealing that meal replacement solutions offer short-term benefits only. This underscores the need for comprehensive and cost-effective lifestyle approaches that involve a balanced nutritioadaptable to regular eating patterns, physical activity, and behavioural motivations for maintaining an ideal weight. Furthermore, post-weight loss management is often overlooked but crucial in preventing relapse and ensuring long-term success. Collaborative efforts with health alliances and other wellness sectors such as physical activity, personal care and beauty, spas, and mental well-being are integral for providing holistic post-weight loss care. In summary, health and wellness are fundamental elements of a holistic strategy for long-term weight loss management, bridging the gap between short-term achievements and sustained overall well-being. Comprehensive programs should transcend mere meal replacements, addressing multifaceted wellness dimensions to empower individuals towards holistic health and lasting success.